Medals And Awards - Charles F. Rand Foundation Fund (83577d80-1204-4870-b017-23943505fadc) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1946)
FRIENDS of the late Charles F. Rand presented in 1930 a sum of money from which the income is available to support various phases of the work of the Institute in which Mr. Rand was so deeply interested. At present the fund amounts to $10,000. The specific terms of the deed of gift are as follows: "The fund collected to establish a memorial to the late Charles F. Rand shall be placed in the custody of the Board of Directors of the American Institute of Mining and Metallurgical Engineers, to be set up as a trust to be known as the `Charles F. Rand Foundation,' the income of which shall each year be applied to a distinct purpose to be decided upon in that year by vote of the Board of Directors. This purpose shall be such as to promote the general welfare of the Institute and to constitute a permanent memorial of the usefulness of Mr. Rand, who for many years gave unstintingly of his time and talents in its service.